2014
DOI: 10.1155/2014/232817
|View full text |Cite
|
Sign up to set email alerts
|

Application of MicroRNA in Diagnosis and Treatment of Ovarian Cancer

Abstract: Ovarian cancer has a poor prognosis because early detection is difficult and recurrent ovarian cancer is usually drug-resistant. The morbidity and mortality of ovarian cancer are high worldwide and new methods of diagnosis and therapy are needed. MicroRNAs (miRNAs) are posttranscriptional regulators of gene expression that are involved in carcinogenesis, metastasis, and invasion. Thus, miRNAs are likely to be useful as diagnostic and prognostic biomarkers and for cancer therapy. Many miRNAs have altered expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 47 publications
0
46
1
Order By: Relevance
“…Accumulating studies have identified a number of miRNAs with aberrant expression in EOC tissues or cells, and indicated that they might be involved into a variety of tumorigenic processes, including cell motility [24]. In the current study, we linked ZEB1 to miR-205, and Based on these findings, we reasonably speculate that overexpression of miR-205 may contribute to ZEB1-mediated tumor progression in human EOCs.…”
Section: Discussionmentioning
confidence: 51%
“…Accumulating studies have identified a number of miRNAs with aberrant expression in EOC tissues or cells, and indicated that they might be involved into a variety of tumorigenic processes, including cell motility [24]. In the current study, we linked ZEB1 to miR-205, and Based on these findings, we reasonably speculate that overexpression of miR-205 may contribute to ZEB1-mediated tumor progression in human EOCs.…”
Section: Discussionmentioning
confidence: 51%
“…PTEN is a negative regulator of PI3K/AKT pathway, thereby being involved in the regulation of apoptosis, DNA damage repair and EMT during embryonic development, cancer progression, and radiotherapy [37][38][39]. Previous study reported that microRNA-214 acts as a potential oncogene in breast cancer by targeting the PTEN-PI3K/Akt signaling pathway [40]. To further explore the molecular mechanisms of tumor radioresistant induced by miR-214, we examined the expression of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…The current study identified multiple microRNAs (miRNAs or miRs) that were differentially expressed in tumor tissue and serum of ovarian cancer patients. These miRNAs have been reported to be important in the occurrence and progression of ovarian cancer, and are expected to be used in early diagnosis, prognosis, recurrence and treatment of ovarian cancer (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%